Extra-Intestinal Manifestations of Coeliac Disease in Children: Clinical Features and Mechanisms - Nardecchia, Silvia; Auricchio, Renata; Discepolo, Valentina; Troncone, Riccardo (Frontiers in Pediatrics, 2019)
Celiac disease (CD) is a systemic autoimmune disease due to a dysregulated mucosal immune response to gluten and related prolamines in genetically predisposed individuals. It is a common disorder affecting ~1% of the general population, its incidence is steadily increasing. Changes in the clinical presentation have become evident since the 80s with the recognition of extra-intestinal symptoms like short stature, iron deficiency anemia, altered bone metabolism, elevation of liver enzymes, neurological problems. Recent studies have shown that the overall prevalence of extra-intestinal manifestations is similar between pediatric and adult population; however, the prevalence of specific manifestations and rate of improvement differ in the two age groups. For instance, clinical response in children occurs much faster than in adults. Moreover, an early diagnosis is decisive for a better prognosis. The pathogenesis of extra-intestinal manifestations has not been fully elucidated yet. Two main mechanisms have been advanced: the first related to the malabsorption consequent to mucosal damage, the latter associated with a sustained autoimmune response. Importantly, since extra-intestinal manifestations dominate the clinical presentation of over half of patients, a careful case-finding strategy, together with a more liberal use of serological tools, is crucial to improve the detection rate of CD.